ปัจจัยที่มีอิทธิพลต่อประสิทธิภาพในการทำงานของบุคลากรในสังกัดองค์การบริหารส่วนจังหวัดเชียงใหม่ - กัญณัฏฐ์ สุนันตา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This Independent Study entitled “Factors Influencing on Work Efficiencies of Officials in Chiang Mai Provincial Administrative Organization” had the objectives of 1) investigating the factors influencing the work efficiency of the officials of Chiang Mai Province Administrative Organizations and 2) studying the efficiency of the officials. The sample group was 264 officials of the Chiang Mai Administrative Organization. The questionnaire constructed by the researcher was used as the tool for data collecting and the data was analyzed using Frequency Distribution, Percentage, Mean and Standard Deviation. The hypothesis was tested by t-test, F-test and Pearson’s Product Moment Correlation Coefficient. The study showed that the factors influencing the work efficiency of the officials of the Chiang Mai Provincial Administrative organization consisted of personal factors, namely age, education levels and the work unit they were affiliated with having a statistical of 0.05 together with work-related factors, namely knowledge related to the duties, organization policies and administration, lines of governance and command, opportunities and advancement, welfare and the working environment with a statistical significance of 0.01.